A Splitting Iteration Method for a Simple Corank-2 Bifurcation Problem (Journal of Computational Mathematics, 1993)
A splitting iteration method is introduced to approximate a simple corank-2 bifurcation point of a nonlinear equation with small extended systems. This iteration method converges linearly with an adjustable speed and needs little extra computational work.